2017
DOI: 10.1186/s13063-017-2246-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of inhaled HYdrogen on neurological outcome following BRain Ischemia During post-cardiac arrest care (HYBRID II trial): study protocol for a randomized controlled trial

Abstract: BackgroundHydrogen gas inhalation (HI) improved survival and neurological outcomes in an animal model of post-cardiac arrest syndrome (PCAS). The feasibility and safety of HI for patients with PCAS was confirmed in a pilot study. The objective of this study is to evaluate the efficacy of HI for patients with PCAS.Methods/designThe efficacy of inhaled HYdrogen on neurological outcome following BRain Ischemia During post-cardiac arrest care (HYBRID II) trial is an investigator-initiated, randomized, double-blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…Due to the small sample size and overall high percentage of favorable outcomes, levels of cytokines were low compared to those in previous reports. (7,44) To further enhance our understanding of this treatment modality, we are currently conducting a large, multicenter, double-blind, randomized control trial in Japan, (45) and the results of this study are expected to reveal the anti-oxidative and anti-inflammatory effect of inhaled H 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small sample size and overall high percentage of favorable outcomes, levels of cytokines were low compared to those in previous reports. (7,44) To further enhance our understanding of this treatment modality, we are currently conducting a large, multicenter, double-blind, randomized control trial in Japan, (45) and the results of this study are expected to reveal the anti-oxidative and anti-inflammatory effect of inhaled H 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that the inhalation of less than 4% hydrogen is practical and safe for patients 14 . A double-blind, randomised control trials using 2% hydrogen inhalation are ongoing 11,24 . Therefore, we believe that the current results may be applicable to clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exhaled H 2 diffuses instantly, without accumulating or resulting in an increased concentration exceeding the inspiratory H 2 concentration. Therefore, 2% H 2 gas can be carefully administered in a hospital (Tamura et al, 2017). During this treatment, a very small number of patients have symptoms such as sparse stool, increased defecation frequency, heartburn, and headache after drinking.…”
Section: Safety Of Hydrogenmentioning
confidence: 99%